Barriers to Implementation of Environmental Management Accounting in South African Small and Medium Enterprises for Sustainable Performance - Nyahuna, Thomas; Doorasamy, Mishelle; Baldavoo, Kiran (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
The key aim of the study is to establish barriers to environmental management accounting (EMA) adoption by manufacturing small and medium enterprises (EMA) in Gauteng province, South Africa from an institutional theory standpoint. To attain the aim of the study 34 in-depth interviews were undertaken with manufacturing SME owners and managers on 34 SMEs. Thematic analysis was adopted to analyze interview transcripts and revealed that lack of government support, financial barriers, lack of incentives to adopt EMA, and absence of guidance to adopt EMA are acting as barriers of SMEs in South Africa from adopting EMA. As a result, the study proposes various incentives such as tax concessions and discounts on eco-materials to encourage SME EMA adoption. Also, the government should take center-stage in making available green training and amplifying awareness of environmental management within SMEs in South Africa. Overall, the study would help regulators and policymakers to align regulations and green strategies with factors that hinder EMA adoption in a ploy to overcome them.